Penetapan kadar flavonoid total ekstrak etanol, fraksi etil asetat dan n-heksan pada daun kakao (Theobroma cacao L.) dengan metode spektrofotometri uv-vis - Zikra Maqfirah; Muhammad Amin Nasution; M. Pandapotan Nasution; Haris Munandar Nasution (Journal of Pharmaceutical and Sciences, 2023)
Cocoa (Theobroma cacao L.)  is a plant that is cultivated on plantations in Indonesia. One part of the cacao plant that has the potential to be developed as a traditional medicine is the cacao leaf because it contains secondary metabolites of flavonoids. Flavonoids have many properties, including acting as antioxidants, protecting cell structures, anti-inflammatories, preventing osteophoresis, and antibiotics. The purpose of this study is to determine the content of secondary metabolites and total flavonoid levels in ethanol extract, ethyl acetate fraction and n-hexane in cocoa leaves. In this study, the initial steps taken are sample collection, sample processing into simplicia, simplicia characterization test then preparation of cocoa leaf ethanol extract by maceration method using 70% ethanol solvent, followed by partitioning process with liquid-liquid extraction method to obtain ethyl acetate fraction and n-hexane and phytochemical screening is carried out. Determination of total flavonoid levels using the UV-vis spectrophotometric method at a wavelength of 437 nm with quercetin as a comparison.The results of this study showed that a cocoa leaf ethanol extract contains alkaloid compounds, flavonoids, tannins, saponins, steroids and glycosides, the ethyl acetate fraction contains alkaloid compounds, flavonoids, tannins, steroids and glycosides, while the n-hexan fraction contains alkaloid compounds, flavonoids and steroids. Total flavonoid levels in cocoa leaves from an ethanol extract amounted to 39.1422±0.0540 mg QE/g, ethyl acetate fraction 45.274±0.0629 mg QE/g and n-hexane fraction 21.4812±0.7048 mg QE/g. The highest flavonoid levels are obtained in the ethyl acetate fraction.